A practical synthesis of substituted 2, 6-diaminopyridines via microwave-assisted copper-catalyzed amination of halopyridines. Issue 42 (21st October 2015) - Mastalir, Matthias; Rosenberg, Egon E.; Kirchner, Karl
Abstract: A microwave assisted copper-catalyzed amination protocol is reported utilizing a series of 2, 6-dihalo- and 2-amino-6-halo pyridine precursors. Using this procedure, selective substitution of one or two halogens by aryl or alkylamines was achieved within 2–6 h with temperatures between 80 and 225 °C affording 2, 6-diaminopyridines in good to excellent isolated yields. The reaction allows easy variation between educts and different N -substitutions. The target compounds are valuable precursors for the synthesis of bis-phosphorylated 2, 6-diaminopyridines which are used as PNP pincer ligands in transition metal complexes. Graphical abstract: A microwave assisted copper-catalyzed amination protocol is reported utilizing a series of 2, 6-dihalo- and 2-amino-6-halo pyridine precursors to yield 2, 6-diaminopyridines in good to excellent yields.